The Spectrophotometric Determination of Thiamine Hydrochloride Drug by Coupling with Diazotized Procainamide - Khansaa I . Abass (Journal of Global Pharma Technology, 2016)
For the determination of thiamine hydrochloride (THC) in both pure and formulated  forms, a simple, sensitive and accurate spectrophotometric method was described. The technique is based on diazotization of the primary amine group of Procainamide with sodium nitrite and hydrochloric acid followed by combining with thiamine hydrochloride to create Light red azo dye showing peak absorption at (502) nm. Beer's law has followed the concentration range (2.5-40) μg.mL‾¹,with (0.1490) μg.mL‾¹ detection limit. The molar absorptivity and Sand ellʾs sensitivity were detected to be respectively (7285.0320) L.mol‾¹.cm‾¹and (0.0463) μg.cm‾². The method for determining in thiamine hydrochloride pharmaceutical preparation has been applied successfully.Keywords: Thiamine hydrochloride, Spectrophotometric determination, Procainamide, Diazotization and coupling.